Psychological Capital And Sustainable Human Resource Management Shape Workforce Balance: Psychological Capital Dan Sustainable Human Resource Management Membentuk Keseimbangan Kerja - Jihan Sulaiman; Fahmi Sulaiman; Kurdeniansyah Kurdeniansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Burnout has become a major workplace challenge because it affects employee psychological well-being, productivity, innovation, and organizational sustainability. Specific Background: This study positions psychological well-being as a central pillar of sustainable human resource development by linking burnout, psychological capital, Job Demands–Resources theory, and Sustainable Human Resource Management. Knowledge Gap: Previous studies have often examined burnout, psychological well-being, psychological capital, and Sustainable Human Resource Management separately, leaving limited conceptual integration between individual psychological resources and organizational sustainability practices. Aims: This article aimed to develop the From Burnout to Balance conceptual model through a Systematic Literature Review using the PRISMA approach. Results: Ten relevant national and international articles published between 2015 and 2025 were synthesized from Scopus, Web of Science, and Garuda. The synthesis shows that burnout can be reduced through two main pathways: strengthening psychological capital and applying Sustainable Human Resource Management. Psychological capital, consisting of hope, efficacy, resilience, and optimism, functions as a protective psychological resource that helps employees cope with work pressure. Sustainable Human Resource Management creates a supportive work ecosystem by prioritizing well-being, work-life balance, and sustainable organizational practices. Psychological well-being is not only an outcome of healthy work conditions but also an indicator of long-term workforce balance. Novelty: The study proposes an integrated multilevel model connecting individual, psychological, and organizational dimensions in one conceptual framework. Implications: Organizations should place employee psychological well-being at the center of sustainable human resource strategies aligned with SDGs 3 and 8. Highlights • Hope, efficacy, resilience, and optimism work as protective resources against work pressure.• Supportive HR practices create healthier, more adaptive organizational ecosystems.• The proposed framework requires further empirical testing across broader work sectors. Keywords Psychological Capital; Sustainable Human Resource Management; Employee Well-Being; Job Demands Resources; Work-Life Balance